The intriguing shapes of the ammonoid whorl - Moron Alfonso, Daniel Andres (2023)
Here we study the variation of the Paleozoic to Mesozoic ammonoid whorl profile shape (WPS, in previous contributions referred as the whorl cross-section shape) employing a geometric morphometric approach, virtual modelling, and statistical tools to assess possible biological phenomena. For this approach, a dataset covering 300 individuals (each belonging to a different genus) was generated from revised specimens and published literature data. From this dataset, we proposed several predictors (e.g., several size parameters) that could be applied in linear models using the principal components (resulting from the geometric morphometric analyses) as response variables. The whorl profile area from the specimens was calculated from virtual models of their original whorls. The results show that the variation in the whorl profile in this sample is resumed by 10 principal components, of which the first three cover 87% of the total variation. PC1 (54.5%) illustrates transformations mainly from the degree of compression and, to a lesser extent, the degree of whorl overlap. Furthermore, the statistical results indicate a significant association between PC1 with several ammonoid subtaxa and whorl size. A correlation between PC1 and the whorl area is also recognised. PC2 (24.8%) reflects morphological transformations that emulates stretching and compression of the whorl profile shape; it is likely related to the hydrodynamic performance of the resulting conch morphology. PC3 (7.4%) encompasses changes on the shape of the venter (from flat to rounded), and the curvature of the flanks, and it seems to be related to minor modifications required to achieve some extreme shapes.